Platón en 90 minutos - Strathern, Paul, 1940- (En 90 minutos., 2014)
Paul Strathern offers a concise account of Plato's life and ideas, and explains their influence on man's struggle to understand his existence in the world. The book also include sections from Plato's work; a brief list of suggested reading for those who wish to push further; and chronologies that place Plato within his own age and in the broader scheme of philosophy.